2023
DOI: 10.3390/ijms241310888
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Opioid Receptors in Addiction and Drug Withdrawal: Where Are We Going?

Abstract: This review article offers an outlook on the use of opioids as therapeutics for treating several diseases, including cancer and non-cancer pain, and focuses the analysis on the opportunity to target opioid receptors for treating opioid use disorder (OUD), drug withdrawal, and addiction. Unfortunately, as has been well established, the use of opioids presents a plethora of side effects, such as tolerance and physical and physiological dependence. Accordingly, considering the great pharmacological potential in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 183 publications
0
4
0
Order By: Relevance
“…Exosomes have been explored for treating drug addiction because they can effectively reach the brain ( 120 ). The mu-opioid (MOR) receptor greatly influences opioids' addictive properties, and it has been suggested that treating opioid addiction by explicitly targeting the MOR could be effective ( 121 ). According to studies, rats without the MOR receptor do not experience the pleasurable benefits of opioids, and MOR antagonists have shown promise in reducing the risk of relapse.…”
Section: Application Of Modified Exosomal Therapeutics Delivery In Brainmentioning
confidence: 99%
“…Exosomes have been explored for treating drug addiction because they can effectively reach the brain ( 120 ). The mu-opioid (MOR) receptor greatly influences opioids' addictive properties, and it has been suggested that treating opioid addiction by explicitly targeting the MOR could be effective ( 121 ). According to studies, rats without the MOR receptor do not experience the pleasurable benefits of opioids, and MOR antagonists have shown promise in reducing the risk of relapse.…”
Section: Application Of Modified Exosomal Therapeutics Delivery In Brainmentioning
confidence: 99%
“…More than 47,000 individuals in the U.S. die annually). [56][57][58][59][60] An individual with an OUD can experience withdrawal when they try to stop their addiction and can experience increased sensations of muscle/skeletal ache, muscular spasms, cravings, skin irritation and constipation. 61,62 These symptoms are an important factor for the continued use of opioids.…”
Section: Effects Of Oud On Physiological Healthmentioning
confidence: 99%
“…A survival analysis of substance abuse relapse found that, in the first six months, the cumulative survival rate was 83%; however, after 24 months, it was 46% and the following time was consistent [7]. Once stopped, there will be an abstinence syndrome (withdrawal symptoms) such as anxiety, sudden changes in temperature, tears, runny nose, sweating, nausea, vomiting, abdominal pain, and diarrhea [8][9][10][11]. Repeated substance abuse induces neuroplastic alternations in dopaminergic neurons in the striatum and midbrain, increasing the neuron's response to the substance rewards, decreasing the susceptivity to non-substance cues and enhancing the susceptivity to tense and dysphoric stimuli [12].…”
Section: Introductionmentioning
confidence: 99%